Pengaruh Harga, Dan Kelangkaan Lpg 3 kg Terhadap Keputusan Konsumen Pada PT. Bengkoelen Berkah Atmosfir di Kecamatan Selebar Kota Bengkulu - Dea Julita; Septi Rindawati; Ovita Charolina (STIA Bengkulu, 2026)
This research aims to find out the Effect of Price, and Scarcity of 3kg Lpg on Consumer Decisions at PT. Bengkoelen Blessed The Atmosphere In A District As Wide As The City Of Bengkulu. The formulation of the problem in this study is: (1) whether the price of 3kg LPG has a significant effect on consumer decisions, (2) whether the scarcity of 3kg LPG has a significant effect on consumer decisions, (3) whether the price and scarcity of 3kg LPG simultaneously affect consumer decisions. The type of research used in this research is a quantitative approach. The population in this study is 3kg lpg consumers. The sample used in this study was 100 respondents taken using the distribution of questionnaires and data analysis techniques. The results of the partial test (t), showed the presence of a Sig value. (0.000) is less than 0.05, this shows that the Price variable has a significant influence on Consumer Decisions. In other words, changes in Price will significantly affect Consumer Decisions. just like Price, because the value of Sig. (0.000) is less than 0.05, this shows that the Scarcity variable also has a significant influence on Consumer Decisions. While the calculated F Value is 27,722. the result of statistical calculations that compare the variations explained by the regression model with unexplained variations (residual). The significance value is 0.000 which is much smaller than 0.05, so it can be concluded that the hypothesis is accepted which means that price, scarcity has a positive and significant effect on consumer decisions at PT. Bengkoelen blessed the atmosphere in a sub-district as wide as the city of Bengkulu. The result of the determination coefficient value of 0.364 means that the price variable, scarcity is able to explain the variation of the consumer decision variable of 36.4% and the remaining 63.6% is influenced by other variables that are not studied. That is, the scarcity of a product or service significantly affects consumer decisions. Suggestions for the next researcher can develop new variables so that the results are more in-depth from the variables studied by the researcher.